SYSTEM APPROACH TO THE BLENDED LEARNING - Kukharenko, В.М. (Journal of Information Technologies in Education (ITE), 2015)
Currently, much attention is paid to the development of learning sour cream – a combination of traditional and distance (30-70%) of training. Such training is sometimes called hybrid and referred to disruptive technologies. Purpose – to show that the use of systemic campaign in blended learning provides a high quality of education, and the technology can be devastating. The subject of the study – blended learning, object of study – Mixed learning process. The analysis results show that the combined training increases the motivation of students,qualification of teachers, personalized learning process. At the same time there are no reliable methods of assessing the quality of education and training standards. It is important that blended learning strategy to support the institutional goals and had an effective organizational model for support.